Effect of myofascial cupping vs integrated neuromuscular inhibition techniques on pain and neck movement in individuals with latent trigger point in trapezius - Preeti Gazbare; Manisha Rathi; Dhanashree Channe (Hong Kong Physiotherapy Journal, 2023)
Background: Pain is the most common symptom for seeking therapeutic alternative to conventional medicine. Trigger points (TrP) being the most debilitating cause of nonspecific neck pain, are found to be more prevalent in trapezius muscle. Various instrument-based and other manual therapy techniques are effective in the treatment of TrP. Objective: To compare the effect of Myofascial Cupping (MFC) and Integrated Neuromuscular Inhibition Technique (INIT) on the upper trapezius latent TrP on pain intensity, pressure pain threshold (PPT) & cervical range. Method: A randomized trial controlled on 40 individuals aged 20–40 years, both gender with latent TrPs in upper trapezius excluding ones who have taken treatment for upper trapezius TrPs within 6 months. Participants were randomly allocated into 2 groups by chit method, one group received MFC and other INIT. Pre- and post-intervention assessment was done using NPRS, pressure algometer and goniometer. Result: Within group, pain has significantly reduced after MFC and INIT with mean difference of [Formula: see text] and [Formula: see text], respectively ([Formula: see text]). PPT increased in both groups ([Formula: see text]) with mean difference of [Formula: see text] and [Formula: see text], respectively. Comparison between the groups showed significant difference in pain intensity ([Formula: see text]) suggesting MFC was more effective in reducing pain. However, a PPT ([Formula: see text]=0.606) and neck lateral flexion to the contralateral side of TrP ([Formula: see text]) were not significant. Conclusion: MFC was more effective than INITs in improving pain, however both interventions showed similar effect on PPT and neck lateral flexion on latent TrP in trapezius.